French-Armenian Resistance hero Missak Manouchian to enter France’s Panthéon - News Wires (France 24, 2023)
Missak Manouchian, an Armenian genocide survivor who went on to become a French Resistance hero, will enter France’s Panthéon mausoleum of revered historical figures next year, President Emmanuel Macron announced in a statement Sunday.
Keywords: 2023-06 June